Pencairan Batubara Peringkat Rendah Papua Menggunakan Katalis Bijih Besi - Talla, Harli; Taba, Herman Tjolleng (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2017)
Low rank coal utilization often adversely affects the equipment used. Distinct with coal liquefaction technology that prioritizes the use of low rank coal. This condition encourages this research, with the aim of observing the liquid potential of low rank Papuan coal by using iron ore catalysts. Papua low rank coal is liquefied on the autoclave 5 liter with iron ore catalyst and antrasen as solvent. Operating conditions consist of temperature of 400C and holding time of 60 minutes. The result of conversion of the three samples without catalyst is only in the range of 65.72-66,45 %, whereas the conversion with iron ore catalysts ranged from 88.63-89.94 % and oil yield between 62.11-63,34%. This result also shows the contribution of iron ore catalyst to increase the conversions that averaged 23.04 %.